Vacuum-Insulated Glazing Assessment by CFD Modeling and Laboratory Measurements - Jacek Schnotale; Giorgio Baldinelli; Francesco Bianchi; Agnieszka Lechowska (Energies, 2025)
This paper concerns measurements and CFD simulations of vacuum-insulated glazing (VIG), which consists of two glass panes separated by a narrow gap from which air has been removed. Distancers, e.g., in the form of small balls, are inserted into this gap every few centimeters to prevent the glass from deflecting. In the first part, simulations of two-pane VIG thermal transmittance with the Ansys Fluent program are described, resulting in thermal transmittance of VIG without the network of distancers equal to 2.18 W/(m2K) and with the distancers equal to 2.29 W/(m2K). The influence of the supports on the thermal transmittance of VIG is also determined. The CFD results show that the supporting balls increase the two-pane VIG thermal transmittance by about 0.15% with respect to the glazing without the distancers. Then, VIG is analyzed both numerically and tested in two measurement stands. Firstly, the tests are performed in a guarded hot-plate apparatus, according to the EN ISO 8302 standard. The two-pane glazing with one low-emissivity coating has a measured thermal transmittance equal to 1.75 W/(m2K). Other measurements were undertaken in the calorimetric chamber equipped with the hot-box apparatus. The results of the numerical assessment are then compared to the measurements of the existing three-pane vacuum-insulated glazing with two low-emissivity coatings, the same as simulated. The procedure follows the EN ISO 8990 standard. Measurement results of 1.10 W/(m2K) are compared to the simulation results of VIG thermal transmittance equal to 1.09 W/(m2K). A satisfactory agreement is reached. Additionally, this paper considers a new correction coefficient to thermal transmittance according to standard EN 673 in order to achieve a proper calculation of vacuum-insulated glazing in the center-of-glass region. The authors propose to use an adjustment coefficient of 1.05 when calculating the thermal transmittance of vacuum-insulated glazing without taking into account convection in the vacuum space and the thermal influence of distancers.